Can you tell me more about your postdoctoral experience? A personal narrative review of the postdoctoral position in the social sciences. (2nd June 2021) - Niang, Anta; Khoury, Emmanuelle; Brunelle, Natacha; Goyette, Martin
Abstract : Purpose: This paper is the result of a collaboration and sharing of experiences of two postdoctoral researchers. The purpose of this paper is to put these experiences into perspective by cross-referencing our respective personal narratives with an analysis of the existing literature on the postdoctoral experience in the social sciences. Design/methodology/approach: The authors conducted a non-exhaustive systematic literature review using the database PsycInfo and the multidisciplinary Web of Science Catalogue database to find relevant articles published from 2000 to today. Of the 946 articles identified from the database, only 12 were included in the literature review. The authors also included four articles identified from other sources, such as Google Scholar. Secondly, the authors used a method inspired by reflexive personal narrative writing, which allowed us to share our postdoctoral experience and examine how it compares or complements the existing literature on postdoctoral experience in the social sciences. Findings: The literature highlights three significant criteria that play a major role in the postdoctoral experience across disciplines: professional identity, work–life balance and relationship with supervisor. While the majority of the current literature seems to highlight the importance of career prospects in the daily lives of postdoctoral researchers, the other two aspects seem to be somewhat less explored. However, personal factors as well as the relationship with the supervisor appear to be of major importance in the search for work–life balance, feelings of competency and overall satisfaction among postdoctoral researchers. Research limitations/implications: At the theoretical level, this paper allows a better understanding of the experiences of postdoctoral students in the social sciences, which seem to be less documented than those in scientific fields (e.g., Science, technology, engineering and mathematics postdoctoral fellow). Practical implications: On a practical level, it constitutes a tool for reflection for postdoctoral researchers in the social sciences as well as for academic actors working to support and develop the well-being of these researchers (e.g. teachers, supervisors, administrators), all with the aim of optimising academic practices. Originality/value: These results are discussed with respect to the specificity that our subjective personal narratives can offer to understand postdoctoral experiences, particularly in the social sciences, and thus offer reflections on ways to attend to individual psychosocial and relational needs that can foster an improved personal and professional training.